APLIKASI DESULFURIZER METODE ADSORPSI DENGAN KARBON AKTIF - Negara, D.N.K.P.; Nindhia, T.G.T.; Widiyarta, I.M.; Nindhia, T.S.; Dwijana, I.G.K.; Dana, I.W.A.R.; Purwadnyana, I.B.P.; Gunawan, I.G.N.W. (Buletin Udayana Mengabdi, 2023)
Biogas produced from cow dung at the Tulus Nadi Livestock Farmer Group in Banjar Gambih, Buahan Village, Payangan District, has been used as cooking fuel. However, the high sulfuric acid (H2S) content of biogas can reduce fuel quality and shorten the life of the biogas stove because H2S causes the components of the biogas stove to rust. This service aims to reduce the H2S content of biogas through the adsorption method, which employs activated carbon as an adsorbent. The service includes practice and instruction in desulfurizer installation, maintenance, and activated carbon regeneration. The test results show that the breeder understands and can use the desulfurizer tool effectively. The desulfurizer can reduce the H2S content to 95.9%, allowing the biogas produced to be used optimally for daily cooking purposes. Keywords: Biogas, adsorption, activated carbon, livestock waste